Metastatic lymph node burden impacts overall survival in submandibular gland cancer - Wang, Lei; Shi, Weihong (Frontiers in Oncology, 2023)
Objective: To assess the effect of the number of positive lymph nodes (LNs) on the overall survival (OS) of patients with submandibular gland cancer (SmGC). Methods: Patients who had undergone neck dissection for SmGC were retrospectively enrolled in this study. The effect of the American Joint Committee on Cancer (AJCC) N stage, the number of positive LNs, LN size, LN ratio, and extranodal extension (ENE) on OS and recurrence-free survival (RFS) was evaluated using Cox analysis. Prognostic models were proposed based on the identified significant variable, and their performance was compared using hazard consistency and discrimination. Results: In total, 129 patients were included in this study. The number of positive LNs rather than LN ratio, LN size, and ENE was associated with OS. A prognostic model based on the number of positive LNs (0 vs. 1–2 vs. 3+) demonstrated a higher likelihood ratio and Harrell’s C index than those according to the 7th/8th edition of the AJCC N stage in predicting OS and RFS. Conclusions: The effect of LN metastasis on OS and RFS was mainly determined by the number of positive LNs. A validation of this finding is warranted in adenoid cystic carcinomas that were not included in this study.